Teoretiс esie study of the object and subject of crime under market conditions and the information society. (Journal of actual problems of jurisprudence, 2016)
This article describes the objects of crimes against property and the author analysed for offences under conditions of market economy and information society. The author of the content of the concepts of «property», «right to property» and «patrimonial» actions. Determined by the ratio between them and assess the adequacy of the consideration of the last two as subjects of crimes. Disclosure of criminal law value of the object and the subject of crimes against property. To produce recommendations for the delin- eation of crimes against property related crimes.
Keywords: subject; object; crimes against property; the prevention of crimes against Property